Learning styles in Higher Education: facing drop out and retention (Práxis Educativa, 2017)
Dropout and retention have been configured today as one of the greatest challenges for Higher Education, not only in Brazil, but worldwide. In this sense, this article presents the results obtained using the learning styles methodology in the development of educational audiovisuals based on the four different styles proposed by Alonso, Gallego and Honey (2007), which are: active, reflexive, theoretical and pragmatic. It is reported in this text the course developed by the group that worked on the project, which surpassed the goals initially outlined in qualitative and quantitative terms, and revealed important and innovative nuances regarding the educational process based on the students’ engagement. It is mainly highlighted here the fact that styles are not labels for student cataloging but rather a teaching methodology that implies a specific didactics. Keywords: Learning styles. Drop out. Retention.